2021
DOI: 10.2147/prbm.s313742
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Product Image Dynamism on Purchase Intention for Online Aquatic Product Shopping: An EEG Study

Abstract: Purpose The normalization of epidemic prevention and control triggered a fierce scuffle in the e-commerce of fresh food, as well as for aquatic products online shopping. The main difficulty for consumers to buy fresh food online has always been information asymmetry. Previous study reported that the image is still the primary information source to address information asymmetry. Yet, few studies have focused on the image presentation of aquatic products in e-commerce. The current study aims to prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…They found that the tiles people preferred elicited higher N100 amplitudes, while those they disliked elicited P200 and LPP amplitudes. Wang et al [15] investigated the effects of the types of images perceived by consumers on their purchase intention and ERP data when buying different types of water products and found that dynamic images of water products stimulated shoppers' positive feelings. The amplitude of N2 decreased, the latency shortened, and the amplitude of LPP increased.…”
Section: Prefacementioning
confidence: 99%
“…They found that the tiles people preferred elicited higher N100 amplitudes, while those they disliked elicited P200 and LPP amplitudes. Wang et al [15] investigated the effects of the types of images perceived by consumers on their purchase intention and ERP data when buying different types of water products and found that dynamic images of water products stimulated shoppers' positive feelings. The amplitude of N2 decreased, the latency shortened, and the amplitude of LPP increased.…”
Section: Prefacementioning
confidence: 99%
“…In this experiment, evoked potentials are EEG signal amplitude variations occurring over a period after the participant observes the product study sample. Segmentation was conducted based on the markers of events, and considering the cognitive process of the brain, this experiment was segmented according to the time range from −200 ms to 800 ms of the stimulus material presentation [55]. For each study sample, the pertinent EEG data spanned a timeframe of 1000 ms, beginning 200 ms prior to and ending 800 ms after sample presentation.…”
Section: Eeg Signalsmentioning
confidence: 99%
“…With the help of quantitative measurement in neuroscience such as electroencephalogram (EEG), these relatively vague concepts can be analyzed and furtherly explore consumer decisions. The most recent studies in neuromarketing have been focused on consumer’s purchase intention and decisions (purchase vs. no-purchase) ( Shang et al, 2020 ; Wang et al, 2021 ), or predicting consumer’s purchases ( Golnar-Nik et al, 2019 ; Bak et al, 2022 ). But fewer studies have gone beyond “buy” and “no buy” and the relative contribution of cognitive and emotional process on consumer motivation ( Aditya and Sarno, 2018 ; Royo-Vela and Varga, 2022 ) and the distinction of consumers decisions have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%